Investigate in operational efficiency of Singapore full licence banks - a translog cost function approach. - Low, See Lien. (2008)
In this research paper, we examine the cost structure of Singapore local full license banks, with special regards to whether scale and/or scope economies exist in these banks. In this study, we categorise these banks into three distinct and separate asset classes. Using the translog cost function model, we found that increasing returns to scale occur for the smallest and medium asset class meaning that for these banks they should merge or get bigger to enjoy economies of scale.